Immediate versus staged complete revascularization in patients with acute coronary syndrome and multivessel disease: a meta-analysis of randomized controlled trials - He, Lin; Yang, Qing-Juan; Sun, Bin; Guo, Cheng; Hu, Ji-Ling; Li, Hong-Pie; Zhao, Jing-Hong; Zhong, Peng-Yu (Frontiers in Cardiovascular Medicine, 2025)
BackgroundA series of trials have confirmed that complete revascularization is more beneficial for patients with acute coronary syndrome (ACS) and multivessel disease than culprit-only revascularization. However, the optimal timing of complete revascularization remains controversial. It is unclear whether immediate complete revascularization is safer and more effective than staged complete revascularization.MethodThis meta-analysis of randomized controlled trials aimed to compare the efficacy and safety of immediate vs. staged revascularization in patients with ACS. The primary outcome was major adverse cardiovascular events (MACE), which were defined as a composite endpoint. Risk ratios (RRs) were calculated using the Mantel–Haenszel (M-H) fixed-effect model. Trial sequential analysis was additionally performed to validate the results. This study is registered with PROSPERO (CRD42023461852).ResultsIn total, 11 randomized studies involving 5,666 patients met the inclusion criteria. At a mean follow-up of 16 months, immediate complete revascularization significantly decreased the incidence of MACE compared with staged complete revascularization [RR: 0.76, 95% confidence interval (CI): 0.66–0.89, P = 0.0004]. Significant decreases were also observed in repeat myocardial infarction (RR: 0.59, 95% CI: 0.43–0.82, P = 0.002), repeat revascularization (RR: 0.62, 95% CI: 0.48–0.79, P = 0.0001), and the composite outcome of myocardial infarction or death (RR: 0.67, 95% CI: 0.48–0.92, P = 0.01). However, no significant differences were found in all-cause mortality (RR: 0.92, 95% CI: 0.64–1.33, P = 0.66) or cardiovascular mortality (RR: 0.96, 95% CI: 0.58–1.61, P = 0.89).ConclusionIn patients with ACS and multivessel disease, immediate complete revascularization significantly decreased the risk of MACE, repeat myocardial infarction, and repeat revascularization, without increasing the risk of all-cause death.